Modeling environmental performance: Green human resource management, leadership, commitment, innovation, and cultural moderation - Rahayu Mardikaningsih; Didit Darmawan; Ong Argo Victoria (Jurnal Fokus Manajemen Bisnis, 2026)
This study investigates the key drivers of environmental performance in micro, small, and medium enterprises in Surabaya, Indonesia, focusing on green human resource management, green transformational leadership, organizational commitment, and green innovation. The research also examines green organizational culture as a potential moderator influencing the relationships between these factors and environmental outcomes. Using a quantitative approach, data were collected from 188 respondents to micro, small, and medium enterprises and analyzed using partial least squares structural equation modeling. The results indicate that organizational commitment has the strongest impact on environmental performance, suggesting that employees who feel a deep connection to and sense of responsibility for their organization are more likely to adopt eco-friendly practices. Green innovation also plays a pivotal role by facilitating the development of sustainable products and processes that enhance resource efficiency. Additionally, both green human resource management and green transformational leadership contribute positively, supporting broader sustainability objectives. Interestingly, the analysis of moderation effects suggests that a highly structured green organizational culture may, in some cases, constrain the influence of green human resource management on environmental outcomes, indicating that overly rigid cultural expectations may not always align with the operational capacities of resource-limited micro, small, and medium enterprises. Overall, the findings emphasize the importance of designing sustainability initiatives that are both strategically ambitious and practically feasible for a small enterprise.